2003
DOI: 10.1016/s1044-0305(02)00814-0
|View full text |Cite
|
Sign up to set email alerts
|

Internal energy deposition in chemical ionization/tandem mass spectrometry

Abstract: The efficiency of the collision-induced dissociation (CID) process as a function of the internal energy deposited into the ion during the ionization event was evaluated. (M ϩ H) ϩ ions of pyrrole, pyrrolidine, pyridine and piperidine (five and six-membered ring heterocyclics) were generated by chemical ionization (CI). The internal energy of the ions was varied by using different reagent gases. Both high-energy (keV) and low-energy (eV) CID were performed on these ions. The experiments showed that the (M ϩ H) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…This large discrepancy between internal energy transfer efficiencies between the two groups should not come as a surprise as there will be a strong dependence on molecular properties, as illustrated by Equation (8). Ospina, Powell, and Yost (2003) demonstrated that both low and high energy CID can be affected by the initial, precollision internal energy of small ions. Forming ions by CI using reagents with different proton affinity values, they were able to generate protonated N-containing heterocyclic ions with different internal energy content.…”
Section: Product Ion Intensity Ratiosmentioning
confidence: 99%
“…This large discrepancy between internal energy transfer efficiencies between the two groups should not come as a surprise as there will be a strong dependence on molecular properties, as illustrated by Equation (8). Ospina, Powell, and Yost (2003) demonstrated that both low and high energy CID can be affected by the initial, precollision internal energy of small ions. Forming ions by CI using reagents with different proton affinity values, they were able to generate protonated N-containing heterocyclic ions with different internal energy content.…”
Section: Product Ion Intensity Ratiosmentioning
confidence: 99%
“…However, nitrogen-containing compounds are polar and may co-elute with phenols during SPE but they usually have very low concentrations . As protonation is the dominant CI mechanism, nitrogen-containing compounds ionized upon methane CI would have even m / z values while the protonated natural phenols have odd m / z values. Therefore, they would have been readily distinguished from the phenols if present in the fuel samples.…”
Section: Resultsmentioning
confidence: 99%
“…An important characteristic of an ion source is the extent of energy that is deposited during ionization. 45 Benzylamonium thermometer ion measurements were used to obtain the extent of internal energy deposition in nanosecond pulsed plasma ionization, conventional microsecond pulsed plasma ionization, and electrospray ionization (refer to the Supporting Information). Electrospray ionization was used as a comparison because is it considered one of the "softest" known ion sources.…”
Section: ■ Results and Discussionmentioning
confidence: 99%